Caracterização morfológica e etiológica da dermatite digital bovina em três regiões da lesão. - Guilherme Vieira Fonseca (2018)
The foot conditions are considered one of the great occurrences in milk cattle, with Digital Dermatitis being the most prevalent infectious disease in semi-intensive herds. Its etiology is still poorly discussed, and although bacteria of the genus Treponema are identified in tissues affected by DD, its etiology has not yet been fully understood. To try to elucidate the morphology and etiology of the disease, 22 animals affected with DD were used. The lesion was excised, the extracted material was sectioned in three different points, being these denominated R1 (center of the lesion), R2 (edge of the lesion) and R3 (skin adjacent to the lesion). For the evaluation of the microbioma of the DD, the In Situ Fluorescent Hybridization (FISH) and new generation sequencing techniques were used and the morphological evaluation was performed macroscopically and histologically. The prevalence of DD found in this study was 29.3%, with 23% of the samples classified as M1, 64% M2 and 14% as M3. The epidermis in R1 and R2, were characterized in 54% and 33.5%, respectively, by moderate areas of tissue proliferation and acanthosis, whereas in R3, slight tissue proliferation was observed. The dermis in R1 and R2, presented moderate increase of inflammatory cells, whereas R3 was characterized by slight increase of inflammatory cells. The bacterial presence in the R1, R2 and R3 was found by 93%, 94% and 76% of the lesions, respectively. Bacteria of the genus Treponema were the most frequent, being present in 88.35% in R1, 84% in R2, and 50% in R3. Dichelobacter nodosus was present in all regions, region 1 with 66%, R2 52% and R3 40%. Fusobacterium necrophorum, present in 44% in R1, 21% in R2 and 25% in R3, and Porphyromonas levii was the least frequent bacterium in the FISH technique, being found 11.7% in R1,16% in R2 and 15% in R3. The bacteria of the genus Treponema were the deepest in the lesion, while P. levii were the most superficial, a fact that occurred in the three regions studied. By the new generation sequencing technique the Treponemas were present as well as Porphyromonas, Mycoplasma, Helcococcus, Corynebacterium, Fusobacterium, Dichelobacter and Alloiococcus. The most frequent treponemal phylo- logy was the unclassified T. followed by T. phagedenis, 67.5% at R1,67,3% at R2 and 62,18% at R3. T. pedis, T. refringes and T. médium were also found. The data found in this study support the concept that the etiology of DD is mainly "multitreponemal" and polymicrobial, where several agents may act synergistically with treponemas to cause DD injury, and further studies are needed to elucidate the real role of each in the etiology of DD.